Pengaruh Dimensi Eksternal Persepsional terhadap Kualitas Layanan Fakultas di Universitas Lampung - Siti Juriyah; Yulianto Yulianto; Noverman Duadji (Cendekia: Jurnal Pendidikan dan Pembelajaran, 2020)
This study aims to see the effect of dimension of the external perception that includes tools of service, the color of service color, uniqueness or stimulus contrast, individual style to attract attention, and moves or service techniques of both partial or simultaneous service made by employees in the Medical Doctor Faculty of Lampung University. This study applied a correlational design that used a questionnaire to collect data. The sample was recruited by 10% from 771 students of Medical Doctor allowing 91 selected at stratified random sampling. Data were analyzed using inferential statistics of linear regression. The hypothesis was tested using SPSS version 19.0. Results show all hypotheses are rejected concluding that there is a significant effect among tools of services, the color of services, uniqueness or stimulus of contrast, individual attraction, moves or techniques of services partially and simultaneously.